Silencing mutations in JAG1 gene may play crucial roles in the pathogenesis of Tetralogy of Fallot - Safari-Arababadi, Amin; Behjati-Ardakani, Mostafa; Kalantar, Seyed Mehdi; Jaafarinia, Mojtaba (Cellular and Molecular Biology, 2018)
JAG1 gene through Notch signaling is implicated in cell fate decisions in early cardiac development, and mutations in several proteins in the pathway have been involved in various disorders. Tetralogy of Fallot (TOF) is the most frequent form of complicated congenital heart disease. The abnormality of TOF begins through the first eight weeks of fetal growth and is confused with ventricular septal defects, obstruction to right ventricular outflow tract, aortic dextroposition, and right ventricular hypertrophy. Hence the existence of mutations in JAG1 gene in Iranian patients with TOF is evaluated. The clinical data and peripheral blood samples were collected from 44 sporadic nonsyndromic patients with TOF and compared to 44 healthy individuals. DNA was extracted, and the exon 6 of the JAG1 gene was amplified by PCR then the PCR products were purified and sequenced. The age range in patients and the control group was 2-36 years, and the mean and standard deviation (SD) of the age in patients was (11.69 ± 7.85 years) and in control group (11.63 ± 7.99 years). Finally, the samples were successfully sequenced, then analyzed and one synonymous variant (c.765C>T; p.Y255Y) was observed in 38 patients with frequency (86.4%) and three controls with frequency (6.8%). The c.765C>T variant is significantly associated with the pathogenesis of TOF in Iranian population.